PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Nurfarina, Amelia; Saputra, Febrian (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
Human resources are the most important asset of a company, in order to achieve the desired goals a company requires good management, especially human resources. Good human resource management is believed to be able to provide optimal performance for the company. This research aims to examine the influence of leadership style and work discipline on employee performance at PT Adi Sarana Armada Tbk (ASSA Rent) Cabang Lampung. This type of research is quantitative research. The population is all 100 employees using a saturated sample. The data collection method used a questionnaire and variable measurement using four Likert scales which were distributed to employees of PT Adi Sarana Armada Tbk (ASSA Rent) Cabang Lampung. Data processing and analysis techniques use validity tests, reliability tests, partial tests (T), simultaneous tests (F), multiple linear regression analysis and coefficient of determination. The research results show that simultaneously, the Leadership Style and Work Discipline variables have a positive and significant effect on the employee performance of PT Adi Sarana Armada Tbk (ASSA Rent) Cabang Lampung. Partially, the Leadership Style and Work Discipline variables have a positive and significant effect on the Employee Performance of PT Adi Sarana Armada Tbk (ASSA Rent) Cabang Lampung